Lipid-polymer hybrid nanoparticles with rhamnolipid-triggered release capabilities as anti-biofilm drug delivery vehicles - Cheow, Wean Sin (2013)
In lung biofilm infection therapies, the use of lipid-polymer hybrid nanoparticles to encapsulate drugs has emerged as a promising alternative to using liposomes because they have superior physicochemical stability and still possess the biofilm affinity and sputum-penetrating ability of liposomes. To be deemed equally efficacious as liposomes against bacterial biofilms, however, the capability of hybrid nanoparticles to target-release encapsulated drugs at biofilm colonies must be demonstrated. This communication details our investigations into the trigger-release characteristics of hybrid nanoparticles in response to encountering rhamnolipids, which are ubiquitously present in biofilm colonies of Pseudomonas aeruginosa, a major respiratory pathogen. Poly(lactic-co-glycolic acid) and phosphatidylcholine were used as the polymer nanoparticle core and lipid coat, respectively. These investigations were performed using compounds from various biopharmaceutical classification systems (BCS) that differ in their lipid-membrane permeabilities. The release of BCS Class III compounds, which have poor lipid-membrane permeabilities, was successfully triggered by rhamnolipids at a concentration approximately equal to their clinically observed value, and this release was attributed to the disruption of lipid coats by rhamnolipid micelles. Not unexpectedly, BCS Class I compounds, which have high lipid-membrane permeabilities, were released freely whether or not rhamnolipids were present. The rate of the triggered release can be controlled by incorporating an additional lipid layer on the hybrid nanoparticles via the electrostatically driven adsorption of lipid vesicles.